A method, system, device and medium for evaluating the failure degree of the super-hydrophobic performance of a mechanically acting anti-pollution flashover coating

CN122904472APending Publication Date: 2026-10-13GUIZHOU POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610766673.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]因此,本发明提供了一种机械作用下防污闪涂层超疏水性能失效程度评估方法、系统、设备及介质解决现有技术中对防污闪涂层的失效评估缺乏对底层物理粘附特征的精准量化,同时又未能适配不同环境因素的问题

Benefits of technology

[0014]本优选技术方案的有益效果为:通过冲击介质的平均质量和瞬时冲击速度计算机械作用冲击动量,并结合基准铺展直径等参数提取环境作用常量,将外部破坏因素与测试液滴自身的铺展特性转化为具体的量化参数;与此同时,利用机械作用冲击动量与环境作用常量共同推导出最终铺展直径,进而计算出固液接触面积,这种基于动力学公式的推算方式,将难以测量的微观受损面积转化为对宏观物理参数的代数运算,避免了主观经验估算带来的偏差,解决了机械作用下防污闪涂层表面接触面积难以客观量化的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122904472A_ABST
    Figure CN122904472A_ABST
Patent Text Reader

Abstract

The application discloses a kind of mechanical action under anti-pollution flash coating super-hydrophobic performance failure degree evaluation method, system, equipment and medium, method includes obtaining the evaluation characteristic parameter of anti-pollution flash coating, according to evaluation characteristic parameter determines the final spreading diameter of test droplet, and based on final spreading diameter determines solid-liquid contact area;Final spreading diameter is differentially calculated, and the calculation result is used as equivalent elastic displacement amount, surface adhesion is calculated in combination with evaluation characteristic parameter;Failure evaluation value is calculated by surface adhesion, solid-liquid contact area and evaluation characteristic parameter, and failure evaluation value is compared with pre-set grading critical threshold, and the failure grade of anti-pollution flash coating is determined.The microcosmic damaged area of the present application is converted into algebraic operation on macroscopic physical parameters, which avoids the deviation caused by subjective experience estimation, and the calculation of failure evaluation value also considers the specific degradation law under different target application environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of performance evaluation technology for anti-flashover coatings, and in particular to a method, system, equipment, and medium for evaluating the degree of failure of the superhydrophobic properties of anti-flashover coatings under mechanical action. Background Technology

[0002] Superhydrophobic anti-flashover coatings are widely used in the external insulation protection of power systems. However, during outdoor service, insulating equipment is subjected to natural mechanical forces such as wind and sand abrasion, rain and snow impacts. These loads continuously damage the microstructure and chemical modification layer of the anti-flashover coating, leading to irreversible degradation of its superhydrophobic properties. If timely and effective condition assessment is not carried out, it can easily cause large-scale power grid flashover faults.

[0003] Currently, failure assessments of the superhydrophobic properties of anti-flashover coatings mostly rely on conventional apparent indicators such as static contact angle. When the microstructure of the anti-flashover coating is damaged by mechanical forces, the test droplets lose their air cushion support and sink into the structure, leading to a significant increase in adhesion. Conventional indicators cannot accurately quantify this expansion of the solid-liquid contact area and the dramatic increase in surface adhesion, thus masking the true extent of damage to the coating. At the same time, the service environment of anti-flashover coatings is complex and variable. For example, the damage mechanisms of chemical corrosion in coastal areas and mechanical friction in windy and sandy areas are completely different. However, existing assessment methods usually use fixed evaluation standards and fail to dynamically adjust the evaluation focus according to the differences in the actual environment, resulting in assessment results that are seriously out of touch with specific operating conditions. Summary of the Invention

[0004] In view of the aforementioned existing problems, the present invention is proposed.

[0005] Therefore, this invention provides a method, system, equipment, and medium for assessing the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action, which solves the problem that the failure assessment of anti-flashover coatings in the prior art lacks accurate quantification of the underlying physical adhesion characteristics and fails to adapt to different environmental factors.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for evaluating the failure degree of the superhydrophobic performance of an anti-flashover coating under mechanical action, comprising: obtaining evaluation characteristic parameters of the anti-flashover coating; determining the final spreading diameter of a test droplet based on the evaluation characteristic parameters; determining the solid-liquid contact area based on the final spreading diameter; performing differential calculation on the final spreading diameter and using the calculation result as an equivalent elastic displacement; calculating the surface adhesion force in conjunction with the evaluation characteristic parameters; calculating a failure evaluation value through the surface adhesion force, the solid-liquid contact area, and the evaluation characteristic parameters; and comparing the failure evaluation value with a preset grading critical threshold to determine the failure level of the anti-flashover coating.

[0007] As a preferred embodiment of the method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action according to the present invention, the step of calculating the failure evaluation value through the surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters includes: determining a first weighting coefficient for the solid-liquid contact area and a second weighting coefficient for the surface adhesion force according to the target application environment of the anti-flashover coating, wherein the sum of the first weighting coefficient and the second weighting coefficient is 1; in response to the target application environment being a chemical corrosion-dominated environment, setting the first weighting coefficient to be less than the second weighting coefficient; in response to the target application environment being a mechanical friction-dominated environment, setting the first weighting coefficient to be greater than the second weighting coefficient; and performing a weighted calculation on the solid-liquid contact area and the surface adhesion force according to the first weighting coefficient and the second weighting coefficient to obtain the failure evaluation value.

[0008] The beneficial effects of this preferred technical solution are as follows: the failure mechanism of anti-flashover coatings differs under different target application environments. Chemical corrosion-dominated environments primarily alter the chemical properties of the anti-flashover coating surface, making changes in surface adhesion the dominant failure characteristic. Conversely, mechanical friction-dominated environments primarily damage the physical structure of the anti-flashover coating, making changes in the solid-liquid contact area the dominant failure characteristic. This preferred technical solution, by setting a first weighting coefficient and a second weighting coefficient summed to 1, adjusts the numerical relationship between the two based on the type of target application environment. This ensures that the weighted failure evaluation value is numerically tilted towards the dominant failure characteristic of the current target application environment, solving the problem that using a fixed evaluation dimension cannot distinguish the failure mechanisms under different working conditions, and ensuring that the evaluation results conform to the degradation law of the coating under specific environments.

[0009] As a preferred embodiment of the method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action described in this invention, the step of weighting the solid-liquid contact area and surface adhesion force according to the first weighting coefficient and the second weighting coefficient includes: collecting the roll-off angle of the test droplet; multiplying the first weighting coefficient by the solid-liquid contact area to obtain a first weighting term, and multiplying the second weighting coefficient, the surface adhesion force, and the cosine value of the roll-off angle to obtain a second weighting term; and summing the first weighting term and the second weighting term to calculate the failure evaluation value.

[0010] The beneficial effects of this preferred technical solution are as follows: When constructing the second weighting term, the cosine value of the collected roll angle is introduced and multiplied by the surface adhesion force. This allows the normal adhesion resistance to be projected onto the direction in which the test droplet actually slides, making the second weighting term reflect the effective resistance that the test droplet needs to overcome when detaching from the anti-flashover coating. This weighted calculation method, which integrates normal mechanical parameters and macroscopic roll parameters, overcomes the deficiency that static indicators alone cannot measure the degree of degradation of the dynamic drainage performance of the anti-flashover coating. The final summed failure evaluation value conforms to the physical detachment mechanism of the test droplet on the damaged anti-flashover coating surface.

[0011] As a preferred embodiment of the method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action described in this invention, the step of comparing the failure evaluation value with a preset graded critical threshold includes: when the failure evaluation value is less than the first critical threshold, the failure level is determined to be normal; when the failure evaluation value is greater than or equal to the first critical threshold and less than the second critical threshold, the failure level is determined to be minor failure; when the failure evaluation value is greater than or equal to the second critical threshold, the failure level is determined to be severe failure.

[0012] The beneficial effects of this preferred technical solution are as follows: the performance degradation of the anti-flashover coating is a continuous physical evolution process. By setting a first critical threshold and a second critical threshold, the continuous failure evaluation values ​​are divided into three tiered failure levels: normal, minor failure, and severe failure, transforming the numerical calculation results into specific engineering operation and maintenance statuses. This mechanism, based on a preset graded critical threshold comparison, not only identifies the severe failure state where the anti-flashover coating has completely lost its superhydrophobic properties, but also captures the minor failure stage where the microstructure of the anti-flashover coating is initially damaged. This overcomes the defects of over-maintenance or delayed early warning caused by a single threshold judgment, ensuring that the output failure level meets the actual needs of differentiated inspection of power equipment.

[0013] As a preferred embodiment of the method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action described in this invention, the step of determining the solid-liquid contact area based on the final spreading diameter includes: ; ; ; ; In the formula, S is the solid-liquid contact area, D is the final spreading diameter, p is the mechanical impact momentum, and n is the environmental constant. The time for complete spreading is given, and m is the mass of the test droplet. The average mass of the impact medium. The instantaneous impact velocity of the impacting medium before contacting the anti-flashover coating. The paving diameter is used as the reference.

[0014] The beneficial effects of this preferred technical solution are as follows: the mechanical impact momentum is calculated by using the average mass and instantaneous impact velocity of the impacting medium, and the environmental constant is extracted by combining parameters such as the baseline spreading diameter. This transforms the external destructive factors and the spreading characteristics of the test droplet itself into specific quantitative parameters. At the same time, the final spreading diameter is derived by using the mechanical impact momentum and the environmental constant, and then the solid-liquid contact area is calculated. This calculation method based on dynamic formulas transforms the difficult-to-measure microscopic damage area into an algebraic operation on macroscopic physical parameters, avoiding the deviation caused by subjective experience estimation, and solving the problem of the difficulty in objectively quantifying the surface contact area of ​​the anti-flashover coating under mechanical action.

[0015] As a preferred embodiment of the method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action as described in this invention, the step of calculating the surface adhesion force in conjunction with the evaluation characteristic parameters includes: ; In the formula, A is the surface adhesion force, and k is the normal elastic coefficient. The initial spreading diameter, This is the equivalent elastic displacement.

[0016] The beneficial effects of this preferred technical solution are as follows: The surface adhesion force of a damaged anti-flashover coating is a microscopic interface interaction force, which is difficult to measure directly in engineering testing. This preferred technical solution, based on the principle of contact mechanics, calculates the difference between the final spreading diameter of the test droplet on the damaged anti-flashover coating and its initial spreading diameter in the undamaged state, defining the macroscopic dimensional change as the equivalent elastic displacement. By multiplying the equivalent elastic displacement by the normal elastic coefficient, which reflects the mechanical properties of the solid-liquid interface, the surface adhesion force is derived using elasticity relationships. This calculation method transforms the microscopic interface force, which is difficult to obtain directly, into an algebraic operation determined by macroscopic geometric parameters and material constants, eliminating the dependence on complex microscopic mechanical testing equipment and solving the problem of objectively quantifying the surface adhesion force after coating damage.

[0017] As a preferred embodiment of the method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action described in this invention, the normal elastic coefficient is calculated as follows: ; In the formula, r is the droplet radius. For the Poisson's ratio of the coating, For the elastic modulus of the coating, For the droplet's Poisson's ratio, Let be the elastic modulus of the droplet.

[0018] The beneficial effects of this preferred technical solution are as follows: By coupling the coating Poisson's ratio and elastic modulus with the droplet Poisson's ratio and elastic modulus, a composite elastic modulus term reflecting the interface characteristics is constructed, and the contact scale is determined in conjunction with the droplet radius. Furthermore, a constant coefficient of four-thirds is introduced into the formula, mapping the theoretical relationship between the rigid contact model and the elastic contact model. This correction considers the physical fact that after the anti-flashover coating's micro / nano structure is damaged, the test droplet's elastic recovery ability weakens and its adhesion behavior tends towards the rigid contact limit. Through the coupling of two-phase material parameters and the correction of the contact mechanics model, the calculated normal elastic coefficient conforms to the mechanical boundary conditions of the damaged coating, avoiding the quantitative deviation caused by the ideal elasticity assumption.

[0019] Secondly, the present invention provides a system for evaluating the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action, comprising: Solid-liquid contact area determination module: used to obtain evaluation characteristic parameters of the anti-flashover coating, determine the final spreading diameter of the test droplet based on the evaluation characteristic parameters, and determine the solid-liquid contact area based on the final spreading diameter; Surface adhesion force calculation module: used to perform differential calculation on the final spreading diameter and use the calculation result as the equivalent elastic displacement, and calculate the surface adhesion force in combination with the evaluation characteristic parameters; Failure level determination module: used to calculate the failure evaluation value through the surface adhesion force, solid-liquid contact area and evaluation characteristic parameters, and compare the failure evaluation value with the preset classification critical threshold to determine the failure level of the anti-flashover coating.

[0020] Thirdly, the present invention provides an electronic device, comprising: Memory and processor; The memory is used to store computer-executable instructions, and the processor is used to execute the computer-executable instructions. When the computer-executable instructions are executed by the processor, they implement the steps of the method for evaluating the failure degree of the superhydrophobic performance of the anti-fouling flashover coating under mechanical action.

[0021] Fourthly, the present invention provides a computer-readable storage medium storing computer-executable instructions, which, when executed by a processor, implement the steps of the method for evaluating the degree of failure of the superhydrophobic performance of the anti-flashover coating under mechanical action.

[0022] Compared with existing technologies, the beneficial effects of this invention are as follows: During the evaluation process, this invention transforms the mechanical effects of the natural environment into basic test parameters such as impact momentum, and derives the solid-liquid contact area by combining the droplet spreading dynamics. Furthermore, based on contact mechanics theory, the differential change in spreading diameter is used as the equivalent elastic displacement, thereby calculating the surface adhesion force. This transformation process directly reflects the physical essence of the droplets losing air cushion support and sinking into the structure after the micro-nano structure of the anti-flashover coating is damaged. It overcomes the limitation of conventional static testing in failing to reflect the true adhesion state of the anti-flashover coating, and achieves objective quantification of the physical damage to the underlying layer of the anti-flashover coating.

[0023] Based on this, and considering the differences in the failure mechanisms of anti-flashover coatings under different target application environments, this invention dynamically adjusts the weighting of the solid-liquid contact area and surface adhesion force calculations according to whether the target application environment is dominated by chemical corrosion or mechanical friction, and incorporates roll-off angle characteristics to directionally correct the surface adhesion force. This dynamic weighting logic avoids the disconnect between operating conditions caused by using fixed evaluation standards, enabling the assessment to adapt to the core failure characteristics under different harsh environments. Finally, the failure evaluation value is calculated through multi-dimensional parameter fusion and compared with the preset grading critical threshold, which can objectively output the true failure level of the anti-flashover coating. Attached Figure Description

[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 This is a schematic diagram of the overall process of the method for evaluating the failure degree of the superhydrophobic performance of the anti-fouling flashover coating under mechanical action according to an embodiment of the present invention. Detailed Implementation

[0026] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the protection scope of the present invention.

[0027] Example 1, referring to Figure 1 As an embodiment of the present invention, a method for evaluating the failure degree of superhydrophobic performance of anti-flashover coatings under mechanical action is provided, including steps S100 to S300: S100. Obtain the evaluation characteristic parameters of the anti-flashover coating, determine the final spreading diameter of the test droplet based on the evaluation characteristic parameters, and determine the solid-liquid contact area based on the final spreading diameter.

[0028] S200. Perform differential calculation on the final spreading diameter and use the calculation result as the equivalent elastic displacement. Combine the evaluation characteristic parameters to calculate the surface adhesion force.

[0029] S300: The failure evaluation value is calculated by the surface adhesion force, solid-liquid contact area and evaluation characteristic parameters, and the failure evaluation value is compared with the preset classification critical threshold to determine the failure level of the anti-flashover coating.

[0030] It should be noted that anti-flashover coatings are widely used in external insulation equipment of power systems. During their long-term outdoor service, they are continuously subjected to the alternating effects of complex natural environments such as wind and sand abrasion, acid rain erosion, salt spray, and ice and snow. This damages the low surface energy chemical structure and micro-nano rough structure of the anti-flashover coating surface, gradually degrading its superhydrophobic properties. Because the damage mechanisms of anti-flashover coatings vary significantly across different geographical environments, single conventional testing indicators are insufficient to accurately quantify the true damage state of the anti-flashover coating, often resulting in incomplete and delayed safety warnings. Furthermore, if the latent loss of superhydrophobic properties of the anti-flashover coating cannot be detected in a timely and accurate manner, it can easily trigger large-scale flashover accidents in humid and polluted environments, seriously endangering the safe operation of the power grid. Therefore, multi-dimensional health monitoring and accurate assessment of the failure degree of anti-flashover coatings are crucial.

[0031] Therefore, to address the aforementioned issues of performance degradation monitoring and quantitative assessment, steps S100-S300 transform complex natural environmental effects into controllable characteristic parameters in the laboratory. Combined with contact mechanics and spreading kinetics models, accurate calculations of the macroscopic solid-liquid contact area and microscopic surface adhesion force are achieved. Simultaneously, by incorporating environmental factors and setting weights, a deep integration of multidimensional damage characteristics of the anti-flashover coating is realized. Ultimately, failure evaluation values ​​matching different application environments are calculated, completing a comprehensive quantification of the performance degradation degree of the anti-flashover coating. Finally, by comparing the failure evaluation values ​​with preset critical thresholds, accurate determination and intelligent early warning of the anti-flashover coating failure level are achieved.

[0032] Example 2, refer to Figure 1 As an embodiment of the present invention, based on the above embodiment, a method for evaluating the failure degree of superhydrophobic performance of anti-fouling flashover coating under mechanical action is provided.

[0033] In this embodiment of the application, step S100 involves obtaining the evaluation characteristic parameters of the anti-flashover coating, determining the final spreading diameter of the test droplet based on the evaluation characteristic parameters, and determining the solid-liquid contact area based on the final spreading diameter. In order to transform the mechanical effects of the natural environment into controllable parameters in the laboratory, researchers will set detailed test conditions according to different simulation scenarios to obtain evaluation characteristic parameters.

[0034] For example, when simulating a dust accumulation scenario, a scratch test or a linear friction and wear test can be used: when conducting a scratch test, a hard indenter is used and the load is controlled at 1~50N and the speed is controlled at 0.5~5mm / s; when conducting a linear friction test, a polymer indenter is used and the load is controlled at 5~20N and the frequency is controlled at 0.5~5Hz. During the test, the contact angle of the anti-flashover coating is monitored in real time. When the contact angle is observed to be lower than 150°, the anti-flashover coating is deemed to have failed.

[0035] In simulating rain and snow splash impact scenarios, a high-speed continuous water jet impact test was adopted, with droplet size controlled at 1~4mm, impact velocity at 5~250m / s, impact frequency at 5~100 drops / second, and the number of impacts set to 10. 3 ~10 8 Second-rate.

[0036] In this embodiment, a sandstorm scenario is used as an example for complete explanation. In the sandblasting test, the compressed air pressure is controlled at 0.1~0.6MPa, the abrasive particle size is 60~120 mesh quartz sand, the impact angle is 15°~90°, and the spray distance is 20~50mm. Under this test environment, a high-speed camera with a frame rate of not less than 10000 frames / second is used to measure the instantaneous impact velocity of the impact medium before contacting the anti-flashover coating, and the average mass of the impact medium is weighed using an electronic balance. To ensure data accuracy, each group of experiments is repeated at least 20 times and the average value is taken. It is assumed that the final measured instantaneous impact velocity is 10m / s and the average mass is 0.05mg. At the same time, environmental action constant calibration is performed. Under a static calibration environment with no external mechanical action (i.e., the impact momentum is 0), a test droplet with a mass of 0.01g is added, and the baseline spreading diameter is measured to be 2 mm, and the complete spreading time is 0.002 seconds.

[0037] The steps for determining the solid-liquid contact area based on the final spreading diameter include: ; ; ; ; In the formula, S is the solid-liquid contact area, D is the final spreading diameter, p is the mechanical impact momentum, and n is the environmental constant. The time for complete spreading is given, and m is the mass of the test droplet. The average mass of the impact medium. The instantaneous impact velocity of the impacting medium before contacting the anti-flashover coating. Based on the spreading diameter; After obtaining the evaluation characteristic parameters, the impact momentum of the mechanical action is first calculated. and environmental constants Then, the final spreading diameter is calculated using the impact momentum from mechanical action and the constant of environmental action. That is, 2.1 mm, and finally the solid-liquid contact area is calculated. .

[0038] It should be noted that although the formula for calculating the environmental constant is a fixed expression, the final value is not a fixed constant. Environmental factors such as temperature, humidity, air pressure, and airflow disturbances directly affect the baseline spreading diameter and complete spreading time of the test droplet. Therefore, in practical applications, it is necessary to collect real-time baseline spreading diameter and complete spreading time under specific test conditions and substitute them into the above formula for separate calibration calculations.

[0039] In this embodiment of the application, step S200 involves performing differential calculation on the final spreading diameter and using the calculation result as the equivalent elastic displacement, combined with the evaluation characteristic parameters to calculate the surface adhesion force. In this embodiment, the process of calculating surface adhesion force deeply integrates classical contact mechanics models with spreading dynamics analysis. First, this invention introduces JKR contact mechanics theory. Under this theoretical framework, the magnitude of the adhesion force when an elastomer undergoes adhesive contact is determined by the balance between elastic deformation and surface energy. Mapping this theory to the actual anti-flashover coating test scenario, it is specifically manifested as follows: when the micro-nano structure of the anti-flashover coating surface is damaged by mechanical action, its surface energy changes, resulting in a significant increase in the spreading diameter of the test droplets on the anti-flashover coating surface.

[0040] This increase in macroscopic size essentially disrupts the original balance between elasticity and surface energy, directly reflecting the expansion of the effective contact area between the test droplet and the anti-flashover coating surface, thus indicating enhanced adhesion. To apply the JKR model to this scheme, this macroscopic dimensional change must be transformed into a computational variable in the mechanical model. Therefore, this embodiment directly performs differential calculations on the final spreading diameter, defining the difference between the final spreading diameter and the initial spreading diameter as the equivalent elastic displacement, thereby successfully establishing a direct physical relationship between the change in spreading diameter and adhesion force.

[0041] It is important to note that after determining the equivalent elastic displacement, when constructing the surface adhesion force formula based on the transformed JKR model, a normal elastic modulus needs to be introduced to describe the elastic recovery behavior of the test droplet. In deriving the normal elastic modulus, the coating elastic modulus, coating Poisson's ratio, droplet elastic modulus, and droplet Poisson's ratio are first incorporated into the calculation to construct a composite elastic modulus term reflecting the solid-liquid interface characteristics. Particularly noteworthy is the introduction of a constant coefficient 4 / 3 in the final expression for the normal elastic modulus. This coefficient originates from the theoretical mapping relationship between the Bradley rigid sphere model and the JKR elastic model in terms of pull-off force values.

[0042] Specifically, the Bradley model describes the contact behavior between a rigid sphere and a plane when only van der Waals adhesion forces are considered, and the corresponding pull-off force expression is: Where R is the radius of the sphere. The JKR model, however, breaks the rigidity assumption and considers the coupling effect of elastic deformation and adhesion forces in elastic contact systems, providing a corresponding expression for the pull-off force. By comparing the two pull-out force expressions, we can obtain... This means that the rigid contact adhesion force predicted by the Bradley model is exactly 4 / 3 times the elastic prediction value of the JKR model. The reason for choosing 4 / 3 as the correction factor in this embodiment is mainly because: when the anti-flashover coating micro-nano structure suffers mechanical damage, the elastic recovery ability of the test droplet will be weakened, which will cause the adhesion behavior of the interface to deviate from the ideal elastic state, thus getting closer to the rigid contact limit situation described by the Bradley model.

[0043] The steps for calculating surface adhesion force by combining evaluation characteristic parameters include: ; In the formula, A is the surface adhesion force, and k is the normal elastic coefficient. The initial spreading diameter, This is the equivalent elastic displacement. The normal elastic coefficient is calculated as follows: ; In the formula, r is the droplet radius. For the Poisson's ratio of the coating, For the elastic modulus of the coating, For the droplet's Poisson's ratio, The elastic modulus of the droplet; In this embodiment, the coating elastic modulus and coating Poisson's ratio can be obtained by in-situ measurement of the anti-flashover coating surface using a nanoindentation testing device, while the droplet elastic modulus and droplet Poisson's ratio can be obtained by standard rheological testing or determined by directly consulting a standard material property table, depending on the specific material of the test droplet.

[0044] Assuming the droplet radius of the test droplet is 0.0013 m, substituting the specific values ​​of various elastic moduli and Poisson's ratios into the above formula, the normal elastic coefficient k is calculated to be 500 N / m. Simultaneously, the experimenters measured the initial spreading diameter of the anti-flashover coating in its undamaged state to be 1.9 mm. Combining this with the final spreading diameter calculated in step S100 as 2.1 mm, a differential calculation yields the equivalent elastic displacement of 0.0021 m - 0.0019 m = 0.0002 m. Finally, substituting the equivalent elastic displacement and the normal elastic coefficient into the surface adhesion force formula, the surface adhesion force is calculated. .

[0045] In this embodiment of the application, step S300 involves calculating the failure evaluation value using surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters, and then comparing the failure evaluation value with a preset grading critical threshold to determine the failure level of the anti-flashover coating. The steps for calculating the failure evaluation value using surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters include A1 to A4: A1. Based on the target application environment of the anti-flashover coating, determine the first weighting coefficient of the solid-liquid contact area and the second weighting coefficient of the surface adhesion force, and the sum of the first weighting coefficient and the second weighting coefficient is 1. In this embodiment, considering the differences in the degradation mechanism of the anti-flashover coating under different geographical and climatic environments, the system incorporates environmental factors when setting the first and second weighting coefficients. Specifically, maintenance personnel or the system backend will first identify the target application environment of the current anti-flashover coating, and assign a first weighting coefficient to the solid-liquid contact area and a second weighting coefficient to the surface adhesion force based on the target application environment. Simultaneously, by setting the sum of the two to 1, it ensures that the weighted calculation result is within a stable dimensional range, facilitating the establishment of a unified evaluation standard.

[0046] A2. In response to the target application environment being dominated by chemical corrosion, the first weighting coefficient is set to be less than the second weighting coefficient. In this embodiment, when the anti-flashover coating is applied to chemically corrosive environments such as coastal salt spray areas or heavy industrial pollution areas, acidic and alkaline substances will chemically react and destroy the low surface energy chemical structure of the anti-flashover coating surface. Under this destruction mechanism, the microscopic geometry of the anti-flashover coating may not have collapsed over a large area, but test droplets can easily adhere to the surface. At this time, the surface adhesion force is much more sensitive to the failure of the anti-flashover coating than the solid-liquid contact area. Therefore, the system sets the first weighting coefficient to be less than the second weighting coefficient to highlight the adhesion failure characteristics caused by chemical corrosion.

[0047] A3. In response to the target application environment being dominated by mechanical friction, the first weighting coefficient is set to be greater than the second weighting coefficient. In this embodiment, when the anti-flashover coating is applied to environments dominated by mechanical friction, such as deserts or areas with strong winds and sandstorms, the sand particles directly damage the micro-nano rough structure of the anti-flashover coating through physical cutting action. This causes the test droplets to lose their air cushion support and become trapped inside the microstructure, resulting in a sharp increase in the solid-liquid contact area, which becomes the most significant failure characteristic. Therefore, the system sets the first weighting coefficient to be greater than the second weighting coefficient. Taking the sandstorm scraping scenario in step S100 as an example, the experimenter set the first weighting coefficient for the solid-liquid contact area to 0.7 and the second weighting coefficient for the surface adhesion force to 0.3 when configuring the system.

[0048] A4. Based on the first and second weighting coefficients, the solid-liquid contact area and surface adhesion force are weighted and calculated to obtain the failure evaluation value. After setting the first and second weighting coefficients, the quantitative calculation stage will officially begin: combining the static weighting strategy with dynamic physical measurement data, and using mathematical calculation logic, transforming the area data representing macroscopic damage and the adhesion force data representing microscopic damage into a single-dimensional failure evaluation value.

[0049] In an optional implementation, the failure evaluation value calculated in step S300 using surface adhesion force, solid-liquid contact area, and evaluation feature parameters can also be obtained by constructing a fuzzy comprehensive evaluation matrix. Specifically, considering that the performance degradation of the anti-flashover coating is a gradual and fuzzy physical process, the system can pre-set multiple membership functions to map the calculated surface adhesion force, solid-liquid contact area, and extracted evaluation feature parameters to different fuzzy state sets such as "intact," "slightly damaged," and "severely damaged." Subsequently, a multi-dimensional fuzzy inference and synthesis operation is performed on these fuzzy state sets using a preset fuzzy rule base. Finally, a continuous numerical value is calculated and output as the final failure evaluation value using a defuzzification algorithm, such as the centroid method or the maximum membership method.

[0050] In another optional implementation, the failure evaluation value calculated in step S300 using surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters can also be obtained by constructing a multidimensional feature vector space and calculating the state offset distance. Specifically, the system can use the surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters corresponding to the undamaged anti-flashover coating as initial feature components to generate a multidimensional baseline state vector. During actual evaluation, the surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters obtained from the current test are simultaneously combined into the current state vector. Then, spatial geometric algorithms such as Euclidean distance are used to calculate the relative offset distance between the current state vector and the baseline state vector in the multidimensional feature space. The magnitude of this relative offset distance directly quantifies the severity of the anti-flashover coating's deviation from its initial healthy state. The system can directly use it as the final failure evaluation value. This calculation method based on spatial geometric distance avoids the bias caused by subjective weight allocation and can more objectively reflect the degradation trajectory of the anti-flashover coating's performance.

[0051] The steps for weighted calculation of solid-liquid contact area and surface adhesion force based on the first and second weighting coefficients include B1 to B3: B1. Collect the rolling angle of the test droplet; The roll-off angle directly reflects the ease with which a test droplet detaches from the anti-flashover coating surface under gravity, and is a key dynamic parameter for evaluating the anti-flashover self-cleaning capability. In this embodiment, researchers used conventional surface tension testing equipment such as the tilt table method to collect the roll-off angle of the test droplet under the current damaged state. Assuming that in a wind and sand rubbing scenario, the roll-off angle of the test droplet on the damaged anti-flashover coating surface was 30°.

[0052] B2. Multiply the first weighting coefficient by the solid-liquid contact area to obtain the first weighting term, and multiply the second weighting coefficient, surface adhesion force and the cosine value of the rolling angle to obtain the second weighting term; In this embodiment, the cosine of the roll-off angle is introduced to correct the surface adhesion force through directional projection when constructing the second weighting term, thus more realistically reflecting the effective adhesion resistance that the test droplet needs to overcome under inclined sliding conditions. Combined with data from a sandstorm scenario, the known solid-liquid contact area is 3.46 mm². 2 The surface adhesion force is 0.1N, the first weighting coefficient is 0.7, the second weighting coefficient is 0.3, and the roll-off angle is 30 degrees. After calculation, the first weighting term is 0.7×3.46=2.422 and the second weighting term is 0.3×0.1×cos30°≈0.026.

[0053] B3. Sum the first weighted term and the second weighted term to calculate the failure evaluation value; In this embodiment, the failure evaluation value is obtained by linearly summing the first weighted term and the second weighted term calculated in step B2: 2.422 + 0.026 = 2.448. The output failure evaluation value is a dimensionless comprehensive index that directly represents the overall health status of the anti-flashover coating.

[0054] In an optional implementation, step S300, which involves weighting the solid-liquid contact area and surface adhesion force based on a first weighting coefficient and a second weighting coefficient, can also pre-set limit reference values ​​for the solid-liquid contact area and surface adhesion force. Then, the actual values ​​of the solid-liquid contact area and surface adhesion force are divided by their corresponding reference values ​​to convert them into normalized coefficients between 0 and 1. Subsequently, the first and second weighting coefficients are used to weight the normalized coefficients to obtain the failure evaluation value. This processing method effectively eliminates calculation biases caused by different physical dimensions, making the final evaluation result smoother and more objective.

[0055] The steps of comparing the failure evaluation value with the preset grading critical threshold include C1 to C3: C1. When the failure evaluation value is less than the first critical threshold, the failure level is determined to be normal. In this embodiment, to ensure intuitive horizontal comparability of evaluation results for different operating conditions and different anti-flashover coating materials, it is necessary to map and limit the effective range of failure evaluation values ​​to [0, 100]. Specifically, if the actual calculated failure evaluation value is less than 0, it is treated as 0; if the failure evaluation value is greater than 100, it is treated as the upper limit of 100, similar to establishing a percentage-based evaluation scale.

[0056] After defining the specified range, the system sets a first critical threshold. Because the anti-flashover coating has extremely stringent requirements for superhydrophobic performance, any slight performance degradation needs to be addressed. Therefore, the boundary between normal and minor failure is set at a relatively low value. In this embodiment, the first critical threshold is set to 3. Combined with the failure evaluation value of 2.448 calculated under the wind and sand erosion scenario, which is less than the first critical threshold of 3, the system determines the current failure level of the anti-flashover coating to be normal, indicating that although the anti-flashover coating has experienced wind and sand erosion, it still possesses good anti-flashover self-cleaning ability.

[0057] C2. When the failure evaluation value is greater than or equal to the first critical threshold and the failure evaluation value is less than the second critical threshold, the failure level is determined to be a minor failure. In this embodiment, the system sets the second critical threshold to 10. The reason for selecting relatively low values ​​like 3 and 10 within the broad range of [0, 100] as the grading boundaries is that the failure evaluation value calculated based on the underlying micromechanical formula is itself of a small magnitude. If the grading value is set too high, such as 50 or 80, most actually damaged operating conditions would be classified as normal by the system, thus completely losing the distinguishability of the warning. When the calculated failure evaluation value falls within the range of 3 or greater and less than 10, the failure level is determined to be a minor failure. For example, if the calculated failure evaluation value is 5.8 under another severe operating condition, this value exceeds the first critical threshold but does not reach the second critical threshold. In this case, the system will indicate that the anti-flashover coating has shown initial degradation and the frequency of on-site inspections needs to be increased.

[0058] C3. When the failure evaluation value is greater than or equal to the second critical threshold, the failure level is determined to be a severe failure. In this embodiment, the second critical threshold represents a safety warning line in anti-flashover engineering applications. Considering the engineering degradation characteristics of the anti-flashover coating, when the failure evaluation value reaches 10, it often corresponds to the contact angle of the anti-flashover coating surface having dropped below 130°. At this point, the anti-flashover coating has essentially lost its superhydrophobic properties and is highly susceptible to leakage current tracking and flashover accidents in humid and polluted environments. Therefore, when the failure evaluation value is greater than or equal to 10, the system determines the failure level to be severe, requiring immediate recoating.

[0059] It should be noted that the first and second critical thresholds are not fixed constants. When there are fundamental changes in the type of anti-flashover coating material, the properties of the test droplets, or the actual service environment, technicians need to re-examine the standard experiments to determine the graded critical values ​​applicable to the new operating conditions in order to ensure the long-term accuracy of the evaluation system.

[0060] In an optional implementation, the comparison of the failure evaluation value with the preset critical threshold in step S300 can also be combined with the service life of the anti-flashover coating to correct the critical threshold. Specifically, when the actual service life exceeds the preset base year, a preset time decay coefficient is extracted; the difference between the actual service life and the base year is multiplied by the time decay coefficient to calculate the threshold compensation amount; then, the threshold compensation amount is superimposed on the initial first critical threshold and the second critical threshold respectively to obtain the corrected first critical threshold and the second critical threshold; finally, the currently calculated failure evaluation value is compared with the corrected first critical threshold and the second critical threshold to determine the failure level.

[0061] In summary, during the evaluation process, this invention transforms the mechanical effects of the natural environment into fundamental test parameters such as impact momentum. It also derives the solid-liquid contact area by combining the droplet spreading dynamics with the test droplet dynamics, and uses the differential change in spreading diameter as an equivalent elastic displacement based on contact mechanics theory to calculate the surface adhesion force. This transformation process directly reflects the physical nature of the droplets losing their air cushion support and sinking into the structure after the micro-nano structure of the anti-flashover coating is damaged. It overcomes the limitation of conventional static tests that cannot reflect the true adhesion state of the anti-flashover coating, achieving an objective quantification of the physical damage to the underlying layer of the anti-flashover coating.

[0062] Based on this, and considering the differences in the failure mechanisms of anti-flashover coatings under different target application environments, this invention dynamically adjusts the weighting of the solid-liquid contact area and surface adhesion force calculations according to whether the target application environment is dominated by chemical corrosion or mechanical friction, and incorporates roll-off angle characteristics to directionally correct the surface adhesion force. This dynamic weighting logic avoids the disconnect between operating conditions caused by using fixed evaluation standards, enabling the assessment to adapt to the core failure characteristics under different harsh environments. Finally, the failure evaluation value is calculated through multi-dimensional parameter fusion and compared with the preset grading critical threshold, which can objectively output the true failure level of the anti-flashover coating.

[0063] Example 3 illustrates a method for assessing the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action. It should be noted that the technical solution of this system for assessing the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action is based on the same concept as the aforementioned method for assessing the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action. Details not described in detail in this example can be found in the description of the aforementioned method for assessing the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action.

[0064] This embodiment also provides a system for evaluating the failure degree of the superhydrophobic performance of anti-flashover coatings under mechanical action, including: Solid-liquid contact area determination module: used to obtain the evaluation characteristic parameters of the anti-flashover coating, determine the final spreading diameter of the test droplet based on the evaluation characteristic parameters, and determine the solid-liquid contact area based on the final spreading diameter; Surface adhesion force calculation module: used to perform differential calculation on the final spreading diameter and use the calculation result as the equivalent elastic displacement, combined with the evaluation characteristic parameters to calculate the surface adhesion force; Failure Level Determination Module: This module calculates the failure evaluation value based on surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters, and compares the failure evaluation value with a preset grading critical threshold to determine the failure level of the anti-flashover coating.

[0065] This embodiment also provides an electronic device suitable for assessing the failure degree of the superhydrophobic performance of anti-flashover coatings under mechanical action, comprising: a memory and a processor; the memory is used to store computer-executable instructions, and the processor is used to execute the computer-executable instructions to realize the method for assessing the failure degree of the superhydrophobic performance of anti-flashover coatings under mechanical action as proposed in the above embodiment.

[0066] This embodiment also provides a storage medium storing a computer program that, when executed by a processor, implements the method for evaluating the degree of failure of the superhydrophobic performance of the anti-fouling flashover coating under mechanical action as proposed in the above embodiment.

[0067] The storage medium proposed in this embodiment and the method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action proposed in the above embodiments belong to the same inventive concept. Technical details not described in detail in this embodiment can be found in the above embodiments, and this embodiment has the same beneficial effects as the above embodiments.

[0068] Based on the above description of the implementation methods, those skilled in the art can clearly understand that the present invention can be implemented using software and necessary general-purpose hardware, and of course, it can also be implemented using hardware. Based on this understanding, the technical solution of the present invention, or the part that contributes to the prior art, can be embodied in the form of a software product. This computer software product can be stored in a computer-readable storage medium, such as a computer floppy disk, read-only memory (ROM), random access memory (RAM), flash memory, hard disk, or optical disk, etc., including several instructions to cause a computer device (which may be a personal computer, server, or network device, etc.) to execute the methods of the various embodiments of the present invention.

[0069] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for evaluating the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action, characterized in that, include: Obtain the evaluation characteristic parameters of the anti-flashover coating, determine the final spreading diameter of the test droplet based on the evaluation characteristic parameters, and determine the solid-liquid contact area based on the final spreading diameter; The final spreading diameter is calculated differentially, and the calculation result is used as the equivalent elastic displacement. The surface adhesion force is then calculated in combination with the evaluation characteristic parameters. The failure evaluation value is calculated by the surface adhesion force, solid-liquid contact area and evaluation characteristic parameters, and the failure evaluation value is compared with the preset grading critical threshold to determine the failure level of the anti-flashover coating.

2. The method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action as described in claim 1, characterized in that, The steps for calculating the failure evaluation value using the surface adhesion force, solid-liquid contact area, and evaluation characteristic parameters include: Based on the target application environment of the anti-flashover coating, a first weighting coefficient for the solid-liquid contact area and a second weighting coefficient for the surface adhesion are determined respectively, and the sum of the first weighting coefficient and the second weighting coefficient is 1. In response to the fact that the target application environment is dominated by chemical corrosion, the first weighting coefficient is set to be less than the second weighting coefficient; In response to the fact that the target application environment is dominated by mechanical friction, the first weighting coefficient is set to be greater than the second weighting coefficient; The failure evaluation value is obtained by weighting the solid-liquid contact area and surface adhesion force according to the first weighting coefficient and the second weighting coefficient.

3. The method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action as described in claim 2, characterized in that, The steps for weighted calculation of solid-liquid contact area and surface adhesion force based on the first and second weighting coefficients include: The roll-off angle of the test droplet was collected; The first weighting coefficient is multiplied by the solid-liquid contact area to obtain the first weighting term, and the second weighting coefficient, surface adhesion force and the cosine value of the rolling angle are multiplied to obtain the second weighting term. The failure evaluation value is calculated by summing the first weighted term and the second weighted term.

4. The method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action as described in claim 3, characterized in that, The step of comparing the failure evaluation value with a preset grading critical threshold includes: When the failure evaluation value is less than the first critical threshold, the failure level is determined to be normal; When the failure evaluation value is greater than or equal to the first critical threshold and the failure evaluation value is less than the second critical threshold, the failure level is determined to be a minor failure. When the failure evaluation value is greater than or equal to the second critical threshold, the failure level is determined to be a severe failure.

5. The method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action as described in claim 4, characterized in that, The steps for determining the solid-liquid contact area based on the final spreading diameter include: ; ; ; ; In the formula, S is the solid-liquid contact area, D is the final spreading diameter, p is the mechanical impact momentum, and n is the environmental constant. The time for complete spreading is given, and m is the mass of the test droplet. The average mass of the impact medium. The instantaneous impact velocity of the impacting medium before contacting the anti-flashover coating. The paving diameter is used as the reference.

6. The method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action as described in claim 5, characterized in that, The steps for calculating surface adhesion force based on the aforementioned evaluation characteristic parameters include: ; In the formula, A is the surface adhesion force, and k is the normal elastic coefficient. This is the initial spreading diameter. This is the equivalent elastic displacement.

7. The method for evaluating the failure degree of the superhydrophobic performance of the anti-flashover coating under mechanical action as described in claim 6, characterized in that, The normal elastic coefficient is calculated as follows: ; In the formula, r is the droplet radius. For the Poisson's ratio of the coating, For the elastic modulus of the coating, For the droplet's Poisson's ratio, Let be the elastic modulus of the droplet.

8. A system for evaluating the failure degree of superhydrophobic properties of anti-flashover coatings under mechanical action, using the method described in any one of claims 1-7, characterized in that, include: Solid-liquid contact area determination module: used to obtain evaluation characteristic parameters of the anti-flashover coating, determine the final spreading diameter of the test droplet based on the evaluation characteristic parameters, and determine the solid-liquid contact area based on the final spreading diameter; Surface adhesion force calculation module: used to perform differential calculation on the final spreading diameter and use the calculation result as the equivalent elastic displacement, and calculate the surface adhesion force in combination with the evaluation characteristic parameters; Failure level determination module: used to calculate the failure evaluation value through the surface adhesion force, solid-liquid contact area and evaluation characteristic parameters, and compare the failure evaluation value with the preset classification critical threshold to determine the failure level of the anti-flashover coating.

9. An electronic device, comprising: Memory and processor; The memory is used to store computer-executable instructions, and the processor is used to execute the computer-executable instructions. When the computer-executable instructions are executed by the processor, they implement the steps of the method for evaluating the degree of failure of the superhydrophobic performance of the anti-fouling flashover coating under mechanical action as described in any one of claims 1 to 7.

10. A computer-readable storage medium storing computer-executable instructions, which, when executed by a processor, implement the steps of the method for evaluating the degree of failure of the superhydrophobic performance of the anti-fouling flashover coating under mechanical action as described in any one of claims 1 to 7.